Cryotolerance of somatic embryos of guinea (Petiveria alliacea) to V-cryoplate technique and histological analysis of their structural integrity - Pettinelli, Jamine de A.; Soares, Bianka de O.; Collin, Myriam; Mansur, Elisabeth Atalla; Engelmann, Florent; Gagliardi, Rachel Fatima (Acta physiologiae plantarum, 2020)
Optimized cryopreservation protocols are essential for the safe, cost-effective and long-term conservation of germplasm of great economic interest, such as Guinea ( Petiveria alliacea L.), a medicinal species that synthesizes a great diversity of bioactive substances, among them polysulfides with antitumor activity. Somatic embryos (SEs) produced from in vitro roots were cryopreserved using the V-cryoplate technique. Their viability was measured using the triphenyltetrazolium test and their recovery by counting the number of secondary SEs produced per cryopreserved SE 90 days after liquid nitrogen (LN) exposure. Structural alterations were evaluated qualitatively and quantitatively during the successive stages of the protocol. SEs were dehydrated in 0.5 M sucrose, attached to cryoplates using sodium alginate solution (3%) and treated with PVS2 for different periods. After immersion in LN, SEs were rewarmed in unloading solution (1.2 M sucrose) at room temperature (25 °C) for 20 min. Viability based on the triphenyltetrazolium test was 100% after 15 min of treatment with PVS2 and LN exposure, and recovery, based on multiplication rate, was 21 somatic embryos produced per cryopreserved somatic embryo after 90 days of culture. The histological analysis of cryopreserved somatic embryos showed plasmolysis in the different cell types after treatment with PVS2, with meristematic and parenchymatic cells presenting a higher plasmolysis level. However, after rewarming, the level of plasmolysis decreased over cultivation time, reaching only 2% in meristematic cells after 30 days, indicating the good ability of Petiveria alliacea SEs to develop cryotolerance under the experimental conditions tested.